Plotting the intertwining psychological and biological pathways linking stress and health - Daly, Michael (Trinity College (Dublin, Ireland). School of Psychology, 2010)
The ability to maintain psychological well-being in the face of exposure to stressors is a crucial capacity that has implications for human health. How a person responds to adverse conditions is contingent on a multitude of interwoven biological and psychological factors. It is my goal in this thesis to outline a broad framework derived closely from the reserve capacity model (Gallo & Matthews, 2003) that specifies and provides empirical support for these relations. I do this by extending the current reserve capacity model and the methodology used to test its core tenets. Specifically, I demonstrate via empirical studies (i) how methodological advancements for the measurement of affect and psychobiological functioning can be used to test and provide support for the model (chapters 2 and 3), (ii) how feedback loops from health to emotion can be addressed in the model (chapters 4 and 5), and (iii) how genetic factors can be incorporated into the reserve capacity model (chapters 6 and 7). This is followed by a general discussion of the main findings, chapter 8. Chapter 2 investigates the relation between affect levels and cardiovascular activity in day-to-day settings using a primary data source of 186 people who completed the Day Reconstruction Method (Kahneman, Krueger, Schkade, Schwarz, & Stone, 2004) and underwent baseline physiological testing and were monitored naturalistically for an entire day. Negative affect was found to predict an elevated ambulatory heart rate and tiredness predicted a lower heart rate. Chapter 3 examines whether a psychosocial resource, self-control, modulates patterns of emotion with likely implications for psychobiological functioning. High trait self-control was associated with stable emotional patterns which partially mediated cortisol and heart rate levels. This study indicated that the capacity to sustain stable patterns of affect across diverse contexts appears to be an important pathway through which self-control relates to health. Chapters 4 and 5 address the idea that health conditions and psychobiological processes can influence well-being. Firstly, morning cortisol levels were shown to predict a steep increase in positive affect from morning through to the evening, particularly among the distressed. Next, in a study based on secondary data from two samples (N = 8190), obesity-related inflammation, as indexed by the acute phase reactant C-reactive protein, was shown to mediate between the presence of obesity and the neurovegetative symptoms of depression. Both of these studies suggest that it may be beneficial to extend the reserve capacity model to incorporate reciprocal relations and reverse feedback processes. Chapters 6 and 7 aimed to investigate if genetic factors can modulate the emotional and health response to life-stressors (based on secondary data, N = 755). The first genetic study tested the role of the apolipoprotein E gene in moderating the influence of an exogenous stressor, an earthquake, on health. Those who experienced damage to their property or were forced to move from their homes as a result of the earthquake had low self-rated health a year later, only if they were apolipoprotein 4 carriers (a dysfunctional lipid transporter). This study indicates support for the proposed extension to include genetic factors in the reserve capacity model. The second gene-stressor interaction study aimed to test if the stress of illness can be modified by both psychosocial and genetic factors. It did this by showing the number of chronic illnesses a person has been diagnosed with interacted with perceived control and variation in the apolipoprotein E gene to predict psychological adjustment. High levels of perceived control appeared to dampen genetic sensitivity to the adverse psychological effects of illness. As discussed in Chapter 8, the results of this thesis support a bidirectional resource model of health where one’s genetic endowment, exposure to stressors, and psychological resources interact to produce patterns of emotion and psychobiological functioning which may lead to the exacerbation of illness.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin